Speak Japanese in 90 days : a self study guide to becoming fluent volume one - Marx, Kevin ([United States] : [Kevin Marx], 2018)
" ... With Speak Japanese in 90 Days, all of the prep work is done for you. Each daily lesson will teach you not only what, but how to study. Speak Japanese in 90 Days is a comprehensive self study guide, and teaches everything you need to know for the JLPT N5 (Japanese Language Proficiency Test) as well as most of the grammar needed for the JLPT N4. It can also be used by intermediate students to brush up on grammar and vocabulary ..."--Amazon.com.
Foreword -- The Japanese Writing System and Pronunciation -- Katakana Words -- Grammar Basics -- Verb Basics -- Intermediate Grammar -- Adjectives -- Numbers, Dates, Time -- Special Words.
Japanese in 90 days : a self study guide to becoming fluent : volume one /, Speak
Keywords: JAPANESE LANGUAGE -- TEXTBOOKS FOR FOREIGN SPEAKERS -- ENGLISH